THE INFLUENCE OF OWN CAPITAL AND PEOPLE'S BUSINESS CREDIT ON MSME INCOME WITH LENGTH OF BUSINESS AS A MODERATION VARIABLE IN GOLEWA DISTRICT, NGADA DISTRICT - Iriany Dewi Soleiman; Sabra B. Wahab; Maria Nestiana Wae (Jurnal Scientia, 2023)
This research aims to examine the influence of the variables Own Capital and People's Business Credit (KUR) on the Income of Micro, Small and Medium Enterprises (UMKM) with Length of Business as a moderating variable among MSME actors in Golewa District, Ngada Regency. This research uses quantitative research with a descriptive approach. The subjects of this research are MSMEs in Golewa District, Ngada Regency. The data used in this research is primary data obtained from respondents who filled out the questionnaire. The sample for this research was 74 respondents who were calculated using the Slovin formula. Data analysis techniques use methodsmoderated regression analysis (MRA).BeBased on the research results, it was found that Own Capital has an effect on MSME Income. People's Business Credit has an effect on MSME Income. Length of Business can weaken the relationship between own capital and MSME Income and also weaken the relationship between People's Business Credit and MSME Income. The contribution of own capital, people's business credit and length of business as moderators of MSME income is 61.1%, while the remaining 38.9% is influenced by other variables outside this research.